EFEK SITOTOKSIK EKSTRAK DIETIL ETER HERBA PEGAGAN EMBUN (Hydrocotyle sibthorpioides Lmk.) TERHADAP SEL KANKER PAYUDARA MCF-7 - Agustina Setiawati; Yohanes Dwiatmaka (Sanata Dharma University, 2015)
Abstract: Triterpenoid saponin, hydrocosaponin A-F, isolated compound from Hydrocotyle sibthorpioides Lmk. performed cytotoxic activity on KB, Daoy and WiDr cancer cells. Methanolic extract of this herb was also investigated in inhibiting cancer development on liver and cervical cancer. Therefore, it is potential to be developed as chemopreventive agent. The objective of this study is to determine cytotoxic activity and compound in diethyl ether extract of Hydrocotyle sibthorpioides Lmk. herbs. The cytotoxic effect of extract on MCF-7 breast cancer cell line was assayed using MTT method while phytochemical analysis was observed using normal phase Thin Layer Chromatoraphy (TLC). Diethyl ether extract of Hydrocotyle sibthorpioides had cytotoxic effect on MCF-7 cells with IC50 365 g/mL. TLC analysis observed that the extract contain flavonoid compounds. Keywords : Hydrocotyle sibthorpioides, MCF-7, cytotoxic, flavonoid